ASSESSMENT OF THE INFLUENCE OF EXPANDED HEMODIALYSIS ON THE RATE OF REMOVAL OF MIDDLE MOLECULAR WEIGHT UREMIC TOXINS - Petrović, Dejan (Medicinski časopis, 2021)
INTRODUCTION. Extended MCO hemodialysis ("Medium Cut-Off") is a method of treatment to replace kidney function, which effectively removes uremic toxins of middle molecular weight from the blood of patients with end-stage chronic kidney disease. AIM. The aim of this study was to examine the effect of expanded hemodialysis on the degree of β2-microglobulin removal. METHOD. Sixteen patients treated with extended MCO hemodialysis were examined. The main parameter for assessing the efficiency of removal of uremic toxins of middle molecular weight is the concentration of β2-microglobulin in the serum before and after a single session of extended MCO hemodialysis. The following were used for statistical analysis: Kolmogorov-Smirnov test, Student's T test for bound samples and Wilcoxon test. RESULTS. Extended MCO hemodialysis effectively removes uremic toxins of middle molecular weight. The reduction index of β2-microglobulin during a single session of extended MCO hemodialysis is 70.60 ± 5.88%. The average loss of albumin during a single session of extended MCO hemodialysis is 1.88 ± 1.02 g/4h, and the index of albumin reduction is 4.94 ± 2.49%. CONCLUSION. Extended MCO hemodialysis effectively removes β2-microglobulin. The β2-microglobulin reduction index is ~ 71% and the albumin loss is less than 4.0 g/4h. This dialysis modality prevents the development of amyloidosis, atherosclerosis and atherosclerotic cardiovascular diseases in the population of patients treated with regular hemodialysis.
Keywords: extended hemodialysis.MCO dialysis membrane.uremic toxins.β2-microglobulin.albumin.